Leptospiral carrier state and seroprevalence among animal population--a cross-sectional sample survey in Andaman and Nicobar Islands. - Sharma, S. (Cambridge University Press, 2003)
A study was conducted with the objective of assessing the leptospiral carrier state and seroprevalence among animal population of Andaman and Nicobar Islands. A total of 494 sera samples from different domestic animals and 85 samples from rats (Rattus rattus) were tested by microscopic agglutination test using nine serogroups prevalent in these islands. Antibodies to leptospires were detected in 164 samples giving an overall seroprevalence of (33.11%). The seroprevalence was highest among cows (40.32%). Of 85 rat (Rattus rattus) samples tested for antileptospiral antibodies six (7.1%) were positive. Leptospires were isolated from kidney of two rats and urine of one cow. Isolate from urine of cow was heavily contaminated and was subsequently lost during further subculture. The two isolates were found to be pathogenic, belonging to serogroup Grippotyphosa. The isolates were further characterized by using a set of monoclonal antibodies. The agglutination patterns of isolates were similar to that of ratnapura and valbuzzi, however these did not completely match.